Sakramen Baptisan Sebagai Dasar Kesetaraan Gender Eksegese Feminis Terhadap Surat Galatia 4:10 - Kainama, Erick; Warella, Sipora Blandina (IAKN AMBON, 2021)
AbstrackThis paper describes the problems that arise in the situation of the church in Galatia, where the problem is more towards the problem of the position of women being secondary. The focus of the text that becomes the reference is Galatians 4:1-10, which only looks at the context of women who are discriminated against using a feminist interpretation method approach. The text was chosen because of the situation of the church in Galatia, where the author not only looks at the andocentric or patriarchal culture, but also the issue of discrimination against women and how baptism is used as a benchmark for it.Keywords: The Sacrament of Baptism, Marginal, Feminist Commentary (Hermeneutics of Suspicion), Galatians 4:1-10AbstrakTulisan ini menguraikan persoalan yang muncul dalam situasi jemaat di Galatia, dimana persoalan tersebut lebih ke arah persoalan kedudukan perempuan yang dinomorduakan. Fokus teks yang menjadi acuan adalah Galatia 4:1-10, yang hanya melihat bagaimana kontekan perempuan yang didiskriminasi itu dengan menggunakan pendekatan metode tafsir feminis. Teks tersebut dipilih karena situasi jemaat di Galatia yang dimana penulis bukan hanya melihat tentang budaya andosentrus atau patriarkhi, tetapi juga masalah diskriminasi terhadap perempuan dan bagaimana baptisan yang dijadikan Paulus sebagai tolok ukur terhadap hal itu. Kata Kunci: Sakramen Baptisan, Marginal, Tafsir Feminis (Hermeneutik Kecurigaan), ajaran Galatia 4:1-10